2023
DOI: 10.1017/s0954422423000069
|View full text |Cite
|
Sign up to set email alerts
|

The use of sentiment and emotion analysis and data science to assess the language of nutrition-, food- and cooking-related content on social media: a systematic scoping review

Abstract: Social media data is rapidly evolving and accessible which presents opportunities for research. Data science techniques, such as sentiment or emotion analysis which analyse textual emotion, provide an opportunity to gather insight from social media. This paper describes a systematic scoping review of interdisciplinary evidence to explore how sentiment or emotion analysis methods alongside other data science methods have been used to examine nutrition, food and cooking social media content. A PRISMA search stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…This novel application of AI techniques in nutritional research aims not only to enrich our understanding of diet-related health outcomes but also to enhance the precision and personalization of dietary interventions. It is our hope that these methodological advancements will encourage further inquiry and innovation at the intersection of technology and nutrition, fostering a deeper, more holistic understanding of the factors that influence dietary choices and their health consequences [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This novel application of AI techniques in nutritional research aims not only to enrich our understanding of diet-related health outcomes but also to enhance the precision and personalization of dietary interventions. It is our hope that these methodological advancements will encourage further inquiry and innovation at the intersection of technology and nutrition, fostering a deeper, more holistic understanding of the factors that influence dietary choices and their health consequences [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…to provide a nuanced understanding of food waste social media data. The importance of interdisciplinary teams has been emphasised in prior research, which found that data science and subject-specific experts should work together to ensure the methods are rigorous, accurate, and relevant to the field of interest [14]. Therefore, this exploratory and data-driven research aimed to analyse food waste discussions on Twitter from an interdisciplinary perspective to identify how food waste is discussed in one part of the exosystem and explore how the conversation evolves over time.…”
Section: Aimsmentioning
confidence: 99%
“…In contrast, these conversations can also be considered when a policy change is made to analyse how the public perceives it [13]. However, current social media research has been small-scale, including methods such as manual content analysis, which typically analyses less than 5000 posts [14] (n = 220 [15], n = 423 [16], and n = 1000 [17]) due to limitations such as the time taken to code the data manually [18,19]. Furthermore, the topics discussed on social media may differ from what a participant would openly share with a researcher in traditional research settings such as focus groups [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on social media related to nutrition has largely focused on engagement (eg, likes, shares, and comments) on a small scale (between 9 social media profile pages and 736 social media posts) using manual analysis by topic experts [29][30][31] and has less frequently explored the breadth of the public's opinions and emotions expressed in social media posts. More recently, sentiment analysis tools, along with additional data science techniques such as topic modeling and social network analysis, were used to explore many nutrition-related topics on social media across 37 studies [32]. Using sentiment analysis alongside other NLP techniques enables researchers to gain a more in-depth understanding of large data sets such as those created in social media, thus providing further insights into potential implications for public health.…”
Section: Introductionmentioning
confidence: 99%